MBG expansion for vulnerable populations in Indonesia: Risk-based readiness across nutrition, safety, and rural implementation - Budiman, Dicky; Chu, Cordia (Program Studi Kesehatan Masyarakat UIN Alauddin Makassar, 2026)
Indonesia’s Free Nutritious Meal Program (Program Makan Bergizi Gratis, MBG) is rapidly expanding in scale, yet evidence on its readiness to serve older adults, persons with disabilities, and rural communities remains limited; this study provides a novel risk-based assessment of expansion readiness across nutritional, disability-specific, food-safety, and rural implementation domains. This study aimed to identify critical implementation gaps and propose a differentiated, phased framework for MBG expansion. A PRISMA-lite literature review was conducted using PubMed and Google Scholar and supplemented by national regulations, government guidelines, Badan Gizi Nasional technical documents, epidemiological surveillance data, and credible media monitoring. Thematic synthesis was undertaken using a risk-based policy framework. Since implementation began in January 2025, 16,109 MBG beneficiaries were reportedly affected by food-borne illness across 70 documented incidents by November 2025, indicating substantial food-safety vulnerabilities. Older adults comprise approximately 12% of Indonesia’s population, with frailty affecting 26.8% in community settings, while approximately 6 million persons with moderate-to-severe disabilities require heterogeneous feeding adaptations. Rural communities face additional barriers involving cold-chain limitations and shortages of certified food handlers. MBG expansion therefore represents a high-consequence policy undertaking requiring beneficiary stratification, condition-specific nutritional and texture standards, strengthened food-safety systems, and outcome-based monitoring. A “Quality First, Scale Later” phased approach is essential to minimize preventable harm.